PENGARUH PENGGUNAAN NR DAN NBR DENGAN BAHAN PENGISI SILIKA TERHADAP SIFAT FISIKA KOMPON ROL KARET CPO - Hari Adi Prasetya (Jurnal Dinamika Penelitian Industri, 2010)
The research aimed to obtain the influence of natural rubber NR, synthetic rubber NBR and alumunium silikat (AISiO₃) as a filler, its physical properties and also to find out rubber compound the best for rubber mixture with variation of NR : NBR 50, 70 : 30, 90 : 10 hr and variation of aluminium silikat (ASiO₂) 45 phr, 50 phr, 55 phr. The result showed that the addition of rubber NR : NBR ratio and alumunium silikat (ASiO₂) had significant effect on the hardness, tensile strength, abration recistance and compression set. The addition of rubber NR : NBR ratio and alumunium silikat (ASiO₂) gave significant effect on the density of the rubber roll CPO compound. The best treatment was found to be the N₂P₂ (the addition of rubber NR : NBR = 70 : 30 phr and alumunium silikat 50 phr) with the rubber roll CPO compound’s characteristics of 78 shore A for hardness, 228 kg/cm2  for the tensile strength, 87,6 kg/cm2 for the abration recistance and 22,60% for the compression set.